Team, Front cover, Editorial information, Table of Content, Back Cover - Journal Editor (Journal of Tropical Pharmacy and Chemistry, 2011)
J. Trop. Pharm. Chem. 2011. Volume 1 Nomor 2 Team, Front cover, Editorial information, Table of Content, Back Cover